2016
DOI: 10.1093/eurpub/ckw116
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported oral health and use of dental services among asylum seekers and immigrants in Finland—a pilot study

Abstract: Despite the small number of participants, our interview-based study indicates that asylum seekers and immigrants have need for acute and basic dental treatment and health education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 13 publications
5
21
0
1
Order By: Relevance
“…This may be associated with level of education because more participants with education at university level reported torture experiences. Other studies suggest that immigrants and asylum seekers with an academic degree more often report the need for dental treatment . The overall need for oral treatment in the current refugee population was high, with visible carious lesions in 89% .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This may be associated with level of education because more participants with education at university level reported torture experiences. Other studies suggest that immigrants and asylum seekers with an academic degree more often report the need for dental treatment . The overall need for oral treatment in the current refugee population was high, with visible carious lesions in 89% .…”
Section: Discussionmentioning
confidence: 90%
“…Thus, it is reasonable to assume that a torture survivor with PTSD symptoms will be more susceptible to triggers during a dental treatment situation and be more prone to develop dental anxiety. In a Finnish pilot study , 56% of asylum seekers claimed to be afraid of visiting a dentist and 44% reported terrifying experiences at dental offices in Finland. Both dental fear and mental stress were more common among asylum seekers than among immigrants in the study group .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental care and treatment are also of concern in these children. 90 Pregnant women are prone to malnutrition, have limited access to antenatal care, and may suffer significant hazards during child birth under poor hygienic conditions with no adequate medical surveillance or treatment. 91 Women are also more susceptible to sexual and genderbased violence (SGBV), especially during forced migration and arrival in refugee camps-both in neighboring and European host countries.…”
Section: Poliomyelitis 120mentioning
confidence: 99%
“…A recent pilot study from Finland demonstrated dental treatment need in most asylum seekers and two-thirds of other immigrants. Access to dental services was considered a major challenge [10].…”
Section: Introductionmentioning
confidence: 99%